In vitro evaluation of a silica whitening toothpaste containing blue covarine on the colour of teeth containing anterior restoration materials. (December 2017) - Philpotts, Carole J.; Cariddi, Eufemia; Spradbery, Paul S.; Joiner, Andrew
Abstract: Objectives: To investigate the effects of a silica-based whitening toothpaste containing blue covarine on the colour of restorations in extracted human teeth. Methods: Human extracted teeth were mounted in acrylic resin. A cavity was cut into the enamel surface and the specimen restored with either glass ionomer or composite dental materials. Following 4 weeks storage in water, specimens were treated with either water, red wine or a toothpaste containing blue covarine (n = 10) for 24 h followed by brushing with a silica-based toothpaste. Specimens were imaged with a digital imaging system at baseline, after 24 h treatment and after brushing with a silica-based toothpaste. CIELAB colour parameters were determined for the restoration and the whole specimen and overall mean colour changes calculated (ΔE). Baseline and post-brushing images were compared subjectively for overall stain and staining around the restoration margin. Results: Red wine produced the largest ΔE values for whole specimens and for all restoration materials and the largest subjective stain scores for whole specimens and restoration margins. The red wine stain was not completely removed by brushing with a silica-based toothpaste. Comparisons of the red wine group with either the blue covarine toothpaste group or the water group were of statistical significance for all parameters (ANOVA, Tukey-Kramer, p<0.05). Following brushing with the silica-based toothpaste, specimens from the blue covarine toothpaste group were not significantly different (p>0.05) to the water group, for all restoration material types. Conclusions: Exaggerated treatment with a blue covarine containing toothpaste does not significantly affect the colour of the restoration or the restoration margin of the dental materials tested versus a water alone treatment. Clinical significance: The silica-based blue covarine containing toothpaste does not permanently stain the restorative materials tested or their margins.